PENGARUH KONSENTRASI ALKOHOL SEBAGAI BAHAN IRIGASI TERHADAP KEKUATAN GESER PELEKATAN SEMEN RESIN PADA DENTIN SALURAN AKAR PASCA PERAWATAN ENDODONTIK DENGAN SILER SENG OKSIDA EUGENOL - , Handy Dwi Lesmana ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this study was to investigate the effect of alcohol concentration as irrigant to shear bond strength of resin cement on root canal dentin after endodontic treatment using zink oxide eugenol sealer. Fourty intact premolar with single root canal were cut at coronal part, leaving 13 mm apical. All teeth were instrumented with step back technique and obtutrated with lateral condensation technique using zink oxide eugenol sealer. All teeth were immerse in saline and stored in 370C incubator for seven days. Post space preparation were done sequently using Pesso reamer number one to five, with nine mm working length. All teeth were randomly devided in four groups of 10 teeth each. The first group using aquades as post space irrigant, second group using 70% alcohol, third group using 80% alcohol and fourth group using 96% alcohol. After irrigation, post space were injected with resin cement and light cure from coronal. All teeth were sliced with diamond disk. First slice was one mm thick, second, third and fourth slices were two mm thick. The second, third and fourth slices were tested for shear bond strength with Universal Testing Machine. Analysis using one-way ANAVA showed alcohol concentration affected significantly to shear bond strength of resin cement (p<0,05). LSD analysis showed a significant difference occurred among all of the treatment groups (p<0.05). The conclution of this study was alcohol concentration as irrigant influenced resin cement shear bond strength on root canal dentin after endodontic treatment using zink oxide eugenol sealer.